E-cigarette or vaping product use–associated lung injury outbreak and public perceptions and trends in smoking cessation discussions on Twitter - Yuqi Zhang; Yingning Wang (PLoS ONE, 2025)
Background Cigarette smokers often use e-cigarettes to quit smoking. The outbreak of e-cigarette, or vaping, product use-associated lung injury (EVALI) in 2019 summer sparked discussions about vaping. However, there is a gap in exploring EVALI’s impact on discussions related to smoking cessation and vaping in smoking cessation on social media. Objective This study examines trends, sentiments, and topics in smoking cessation discussions before, during, and after EVALI. Methods English tweets from September 1, 2018, to January 31, 2020, were collected using snscrape, filtered for smoking-cessation-related keywords. Sentiments were assessed with Valence Aware Dictionary and sEentiment Reasoner (VADER), categorizing tweets as positive, negative, or neutral. Topics were identified via Latent Semantic Analysis, and LexRank was used to extract representative sentences for qualitative insights into the discussions. Results Among 397,528 smoking cessation-related tweets, discussions significantly increased in September 2019, accompanied by a decline in sentiment scores. Five topic groups—“Vaping”, “Cannabis”, “Stop Smoking”, “Gum”, and “Tobacco”—were identified. “Vaping” dominated the entire timespan, surpassing other topics in volume. Sentiment scores decreased for “Vaping”, “Stop Smoking”, and “Cannabis” in September 2019, while remaining stable for “Gum” and “Tobacco”. Representative sentences showed that despite the EVALI outbreak, many individuals still perceived vaping as an effective smoking cessation tool and oppose tobacco control policies targeting e-cigarette flavors. Conclusions The results deepen our comprehension of how perceptions regarding smoking cessation evolve during EVALI, offering insights for refining public health communication strategies in future health crises.